Validity of intraoral soft tissue landmarks as reference points for orientation of occlusal plane in natural dentition: A clinical study - Shefali Singla; Manu Rathee (Wolters Kluwer Medknow Publications, 2015)
Introduction: Occlusal plane is the average plane established by incisal and occlusal surfaces of teeth. Various anatomic landmarks are used to determine this missing component of occlusion which is lost with the loss of teeth. However, variation has been observed in the orientation of occlusal plane determined clinically with different anatomical landmarks as references. Objective: This study was undertaken to determine the relation of intraoral anatomic soft tissue landmarks, namely, retromolar pad and parotid papilla with occlusal plane in natural dentition. Materials and Methods: Irreversible hydrocolloid impressions of 100 edentulous individuals (50 males and 50 females) were made to get the models. A 16 gauge wire was extended from mandibular occlusion plane posteriorly up to retromolar pad to establish their relationship. Furthermore, vertical distance of apex of parotid papilla to maxillary molar cusp tip it opposed (distobuccal cusp of maxillary first molar or mesiobuccal cusp of maxillary second molar), and mandibular molar cusp tip (to which parotid papilla apposed) was measured when the teeth were in maximal intercuspal position. Results: This study determined that the natural occlusal plane is oriented posteriorly at the level corresponding with the lower third of retromolar pad. Mean distance of parotid papilla above the corresponding maxillary cusp tip (while in occlusion) was 5.048 mm, and mean distance of Parotid papilla above the corresponding mandibular molar cusp tip (while in occlusion) was determined to be 3.602 mm. The difference in observed means between males and females or between right and left side was not statistically significant.